Posterior fusion in Pott's disease of children - Bayındır, Şükrü; Baytok, Gürbüz; Tokgözoğlu, Nejat; Göğüş, Talat (The Turkish Journal of Pediatrics, 1969)
An evaluation was made of 71 children between the ages of 0 and 16 with Pott’s disease who visited Hacettepe Faculty of Medicine between 1961 and 1967. The location of the disease, the number of vertebrae affected and the ages of the patients are studied.We found that Pott’s disease develops extremely rapidly in the early years of childhood, with such complications as paraplegia and extreme deformity, and the importance of early diagnosis and treatment is emphasized.The value of posterior fusion, which was performed on 63 of our patients, and its results are described. The value of conservative treatment by bed-rest in paraplegic cases is also shown. If, however, there is no improvement after one month, such surgical methods as antero-lateral decompression and abcess drainage were found to be necessary. It is also observed that when paraplegia disappeared after conservative and surgical treatment, its recurrence could be prevented by posterior fusion.We suggest that if a modified form of Hibbs’ technique is used, leaving the spinous processes in place and decorticating them with the laminae, posterior fusion is achieved more completely in a shorter time.